Cardiotoxicity in Biological Agent-Targeted Therapy for Rheumatoid Arthritis: ADR Signal Mining and Analysis of Food and Drug Administration Adverse Event Reporting System Database - Tang, Xiaoyan; Xu, Xiaolin; Li, Ji; Zhao, Bin (Frontiers in Pediatrics, 2021)
Purpose: Biologic agent-induced cardiotoxicity is markedly concerning. Rheumatoid arthritis (RA) treated with biologic agents is known to have the potential for cardiotoxicity; however, existing clinical evidence is not adequate to explain real-world patterns of cardiotoxicity. In this study, we quantify the risk of cardiotoxicity in patients with rheumatoid arthritis treated with biological agents. Methods: Cardiotoxicity reports induced by four types of biologic agents, abatacept, adalimumab, tocilizumab, and etanercept were used to mine data from the FDA's adverse event reporting system (FAERS) database from January 1, 2004 through September 30, 2020. Reports of cardiotoxic events were analyzed using a reporting odds ratio (ROR) algorithm, the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), the multi-item gamma Poisson shrinker (MGPS), and logistic regression methods. We use the preferred term of the Medical Dictionary of Regulatory Activities to identify such events. Results: A total of 3,969 reports of cardiotoxic events were identified involving biologic agents used for RA as the suspect drugs in this study, 317 reports of abatacept, 2,137 reports of adalimumab, 273 reports of tocilizumab, and 1,242 reports of etanercept. Adalimumab was the most reported, followed by etanercept. The proportion of death and disability outcomes reported for each targeted treatment represents approximately 20–25% of the total reported severe adverse events. In addition, relatively low cardiotoxicity reporting rates were found with abatacept. Conclusion: Analysis of FAERS data offers a more precise profile on the characteristics and occurrences of cardiotoxic events. The findings are a clinical reminder to physicians that an increased vigilance concerning the cardiotoxic effects of biological agents needs to be implemented. Also, more comparative studies are required in the future to explain the mechanisms that cause these cardiac phenomena.